Suddenly a stay-at-home dad? Short- and long-term consequences of fathers' job loss on time investment in the household - Juliane Hennecke; Astrid Pape (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Commonly described as the "gender care gap", there is a persistent gender difference in the division of domestic responsibilities in most developed countries. We provide novel evidence on the short- and long-run effects of an exogenous shock on paternal availability, through a job loss, on the allocation of domestic work within couples. We find that paternal child care and housework significantly increase in the short run on weekdays, while we do not see any similar shifts on weekends. Effects are positive and persistent for fathers who remain unemployed or have a working partner, but reverse after re-employment. We also find significant changes for female partners as well as in the cumulative household time investments and the outsourcing of tasks, depending on the labor force statuses of both partners. We theoretically discuss time availability and financial constraints, relative bargaining powers, gender role attitudes, and emotional bonds as potential explanations for the effects.
Keywords: J13; J22; J63; 330; job loss; paternal child care; fatherhood; domestic labor; intra-household allocation